ВИЗНАЧЕННЯ ПОТУЖНОСТЕЙ ЗА НЕСИМЕТРИЧНИХ РЕЖИМІВ ТРИФАЗНИХ МЕРЕЖ ІЗ ЗАЗЕМЛЕНОЮ НЕЙТРАЛЛЮ - Бурбело , М.Й.; Мельничук , С.М. (Інститут електродинаміки НАН України, Київ, 2015)
In the article application of integrated and instantaneous power in unbalanced three-phase network with grounded neutral to negative and neutral sequences is proved. It is shown that the asymmetry modes on the reverse sequence should be characterized by complex and instant apparent power of the negative sequence. Expressions for integrated and instantaneous conditional power in unbalanced three-phase network with grounded neutral to negative and neutral sequences are obtained. Connection between instantaneous conditional power with voltages and currents positive, negative and zero sequence are found. References 8, figures 2.